1997
DOI: 10.1093/jat/21.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cocaine and its Metabolites in Amniotic Fluid and Umbilical Cord Tissue

Abstract: The increased use of cocaine by women of child-bearing age has left many health care scientists searching for improved methods of detecting prenatal cocaine exposure. To that end, a study of the determination of cocaine and its metabolites in amniotic fluid and umbilical cord tissue was undertaken. Amniotic fluid (n = 32) and umbilical cord tissue (n = 70) specimens were collected from pregnant subjects admitted to labor and delivery at Shands Hospital at the University of Florida (Gainesville, FL). Subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 14 publications
0
17
0
2
Order By: Relevance
“…However, because only a small percentage of cases had reported maternal drug-use and the specific drugs that were used were unique to each case, we cannot conclude with any certainty whether this finding has a biological basis or is due to chance. It is nevertheless interesting to note that the drugs reported in our study by case mothers are known to cross the placenta, [28][29][30] that NB cells express the serotonin receptor, 5-HT 3 31 that can bind fluoxetine and cocaine, 32,33 and that maternally derived serotonin has been shown to regulate gene expression, proliferation, migration and morphogenesis of neural crest cells, from which NB derives, in mouse embryos. 34 Whether drugs, particularly those that act in the serotonin pathway, can influence malignant transformation of neural cells has not been examined.…”
Section: Discussionmentioning
confidence: 76%
“…However, because only a small percentage of cases had reported maternal drug-use and the specific drugs that were used were unique to each case, we cannot conclude with any certainty whether this finding has a biological basis or is due to chance. It is nevertheless interesting to note that the drugs reported in our study by case mothers are known to cross the placenta, [28][29][30] that NB cells express the serotonin receptor, 5-HT 3 31 that can bind fluoxetine and cocaine, 32,33 and that maternally derived serotonin has been shown to regulate gene expression, proliferation, migration and morphogenesis of neural crest cells, from which NB derives, in mouse embryos. 34 Whether drugs, particularly those that act in the serotonin pathway, can influence malignant transformation of neural cells has not been examined.…”
Section: Discussionmentioning
confidence: 76%
“…In the literature, only cocaine and metabolites’ concentrations in umbilical cord has been published. Moore et al [44] reported one case with a concentration of 1200 ng/g for benzoylecgonine in umbilical cord, and Winicker et al [46] 13 specimens where the main metabolite was benzoylecgonine (up to 1237 ng/mL) followed by ecgonine methyl ester (up to 52ng/mL). Keeping in mind these data, it is possible that compounds are concentrated in meconium or umbilical cord according to physicochemical properties (less lipophilic umbilical cord, more lipophilic meconium).…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations were measured by a meconium method [11, 45], or validation data were not supplied for the umbilical cord matrix [44]. Only Winecker et al [46] developed a cocaine quantification method in umbilical cord specimens. In order to obtain reliable data, the analytical method employed has to be fully validated in a given biological matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of organochlorine compounds [including dichlorodiphenyldichloroethylene (DDE) and dichlorodiphenyltrichloroethane (DDT)], therapeutic and illegal drugs, first-hand and environmental tobacco smoke, dust mite allergens, and metals indicate that toxicants are detectable in amniotic fluid and are likely to reflect fetal exposures (Carvalho et al 2001;Foster et al 2000;Holloway et al 2000;Jauniaux et al 1999;Kim et al 1998;O'Leary et al 1970;Polishuk et al 1977;Talbot et al 1988;Winecker et al 1997). To date, no studies have investigated levels of common nonpersistent pesticides in amniotic fluid.…”
mentioning
confidence: 99%